Answer:
108 - 30x - 116x² - 18x³
Step-by-step explanation:
We have to get the value of - (2x + 12) (9x² + 4x - 9)
Now, using the distributive property of multiplication we get
- (2x + 12) (9x² + 4x - 9)
= -[2x (9x² + 4x - 9) + 12 (9x² + 4x - 9)]
= -[(18x³ + 8x² - 18x) + (108x² + 48x - 108)]
= -[18x³ + 116x² + 30x - 108]
= 108 - 30x - 116x² - 18x³ (Answer)
Answer:
2
Step-by-step explanation:
Answer:
5√(10/x)
Step-by-step explanation:
√10^3/4x
= √10^3 / √4x
= 10√10 / 2√x
=(10/2)√(10/x)
= 5√(10/x)
Answer:
Not larger or smaller; the areas are the same
Step-by-step explanation:
Recall that the formula for the area of a triangle of base b and height h is
A = (1/2)(b)(h).
In the first case, h = 3 ft and b = 2.5 ft. This results in an area of 3.75 ft^2.
In the second case, h = 2.5 ft and b = 3 ft. The area is the same: 3.75 ft^2.
This is because A = (1/2)(b)(h) has the same value regardless of the order in which b and h are used as multipliers.
There is no difference in the areas of the two signs. The areas are the same.